2015
DOI: 10.12968/ijpn.2015.21.8.400
|View full text |Cite
|
Sign up to set email alerts
|

Palliative care in dementia: literature review of nurses' knowledge and attitudes towards pain assessment

Abstract: Nurses play a key role in the effective management of pain through the use of pain assessment tools, behavioural observation, and analgesic choice. Pain assessment in dementia remains challenging for nurses due to the complexity and individualisation of pain behaviours. The accessibility of appropriate training, workforce stability and a standardised approach to pain assessment are key to the successful management of pain in older people with dementia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 40 publications
(88 reference statements)
2
39
0
3
Order By: Relevance
“…However, evidence has suggested that overreliance on personal knowledge and collateral information alone may also prove an inadequate approach to pain assessment if attitudes towards the patient population are negative, the patient is unknown or unfamiliar to the care team, or staff are inexperienced in recognising the behavioural indicators of pain in people dying with dementia . Other studies have identified a need for nursing home staff to receive ongoing, regular training, and support in developing pain assessment protocols, conducting pain assessments and responding appropriately to the outcome …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, evidence has suggested that overreliance on personal knowledge and collateral information alone may also prove an inadequate approach to pain assessment if attitudes towards the patient population are negative, the patient is unknown or unfamiliar to the care team, or staff are inexperienced in recognising the behavioural indicators of pain in people dying with dementia . Other studies have identified a need for nursing home staff to receive ongoing, regular training, and support in developing pain assessment protocols, conducting pain assessments and responding appropriately to the outcome …”
Section: Discussionmentioning
confidence: 99%
“…[35][36][37] Other studies have identified a need for nursing home staff to receive ongoing, regular training, and support in developing pain assessment protocols, conducting pain assessments and responding appropriately to the outcome. [38][39][40] Participants believed that health policy and other clinical directives were misdirected in focusing on simple tools in a clinical area widely recognised as challenging and highly complex. Failure to highlight the benefits of using OPTs and lack of guidance on how they might be integrated with existing practice were other criticisms raised.…”
Section: Phys015 Male Consultant Palliative Medicine Hospicementioning
confidence: 99%
“…Pain in people with dementia, with and without intellectual disability, is often underdetected and undertreated (Burns & McIlfatrick, 2015;Cohen-Mansfield, 2014). A self-report of pain is the gold standard in pain management (McCaffery & Beebe, 1989;Pasero & McCaffery, 2010;Twycross, Voepel-Lewis, Vincent, Franck, & Baeyer, 2015).…”
Section: Backg Rou N Dmentioning
confidence: 99%
“…Pain behaviours can be complex and individualised and can be associated with depression, functional impairment and agitated behaviour 15. Clinically, recognising distress is an important first step 16.…”
Section: Assessment and Management Of Symptomsmentioning
confidence: 99%